IMPLEMENTATION OF PROFESSIONAL ETHICS OF LIBRARIANS FROM AN ISLAMIC PERSPECTIVE - Lubis, Nur Afni; Ritonga, Sakti (Academic Solution Publisher, 2023)
The purpose of this research is to describe the professional ethics of librarians in the library of Universitas Islam Negeri (UIN) Sumatera Utara in terms of an Islamic point of view and explain the form of professional ethics based on Islamic values applied by librarians at the Library of the State Islamic University of North Sumatra. The method of this research is used a descriptive research method with a qualitative approach. This research was used data collection techniques of observation, interviews, and documentation. The ethics of the librarian profession from an Islamic point of view are being fair to library visitors, cooperating and helping each other among colleague librarians, and being responsible for the mandate of the tasks carried out. Describe the implementation of librarian professional ethics in the library of the UIN Sumatera Utara in terms of an Islamic point of view. The forms of professional ethics applied by UIN Sumatera Utara’s librarians are ethics about recognizing users and paying attention, ethics being flexible and polite, and ethics about being communicative and being honest.